2019
DOI: 10.1017/ipo.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

When ethnic prejudice is political: an experiment in beliefs and hostility toward immigrant out-groups in Italy

Abstract: When the immigration issue has been strongly politicized, prejudice toward minority out-groups can be profoundly imbued with politics, to the point that citizen responses to partisan cues about immigrants tend to operate on the basis of a ‘political sympathy/antipathy bias’. This article demonstrates that there is a direct causal relation between the nature (i.e. contents and sources) of political communication over immigrants and voters' responses. Drawing on an experimental design based on ITANES (Italian Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We choose to consider two different outgroups because of the desire to generalize the hypotheses across toward two outgroups defined in terms of ethnicity or religious affiliation. Recent literature has shown that hostility toward immigrants in Italy is ethnicity-blind, and is thus not more pronounced toward ethnic groups than toward religious groups such as Muslims (Barisione, 2020). Moreover, considering the theoretical background behind cultural humility, we consider cultural humility as able to prompt the appreciation of cultural diversity over and above the criteria that defines such diversity (e.g., religious, ethnic diversity).…”
Section: Overview and Hypothesesmentioning
confidence: 97%
“…We choose to consider two different outgroups because of the desire to generalize the hypotheses across toward two outgroups defined in terms of ethnicity or religious affiliation. Recent literature has shown that hostility toward immigrants in Italy is ethnicity-blind, and is thus not more pronounced toward ethnic groups than toward religious groups such as Muslims (Barisione, 2020). Moreover, considering the theoretical background behind cultural humility, we consider cultural humility as able to prompt the appreciation of cultural diversity over and above the criteria that defines such diversity (e.g., religious, ethnic diversity).…”
Section: Overview and Hypothesesmentioning
confidence: 97%
“…Interestingly, leftists seem to be more sensitive to humanitarian vis-à-vis instrumental reasons and less concerned about immigrants' religious identity than their right-wing fellow citizens (Bansak et al ., 2016). Coming to the Italian context, experiments covering this topic are rare, with exceptions showing a link between ideology and party alignments, on the one hand, and partisan cue-taking and ethnic prejudice, on the other (Barisione, 2020).…”
Section: A Factorial Experiments On Preferences Towards Asylum Seekersmentioning
confidence: 99%
“…Thus, one factorial experiment might help disentangle what factors matter the most for asylum-seeker acceptance, whether there is an interplay among instrumental, humanitarian and ethnic considerations, and to what extent, if any, political ideology moderates their relationships. Although the following example is merely illustrative, available research (Bansak et al ., 2016; Barisione, 2020) leads us to believe that Italians would look more favourably at asylum applications pursued by skilled immigrants rather than low-skilled ones (h1); by those escaping war as compared to those coming for economic opportunities (h2); or by subjects from Christian-majority countries against Muslim-majority ones (h3).…”
Section: A Factorial Experiments On Preferences Towards Asylum Seekersmentioning
confidence: 99%
“…As some studies have remarked (e.g., Bianco et al., 2021 ; Clissold et al, 2020 ; Giacomelli et al, 2020 ; Gordils et al, 2021 ; Hartman et al, 2021 ), concerns about an invisible enemy, such as a virus, can indeed lead to the emergence of feelings and behaviors of social exclusion by the political world, the media, and by people in their daily lives. In recent decades, Italy has been a destination, both temporary and permanent, for immigrants coming mainly from Africa and this has led to a re-surfacing of feelings, attitudes, and behaviors openly hostile toward these minorities ( Barisione, 2020 ; Passini & Villano, 2018 ). In Italy, as well as in other countries, the current pandemic seems to have exacerbated these feelings and increased discrimination against migrants ( Bianco et al, 2021 ; Gordils et al, 2021 ).…”
mentioning
confidence: 99%